The Contribution Of Waqf Forests On Sustainable Development Goals - Ayif Fathurrahman (ITB AAS INDONESIA Surakarta, 2023)
Forest waqf is one of the efforts to help achieve the goals of Islamic economics. Therefore, this paper aims to; first, describe how the establishment of Bogor Forest Waqf. Second, describe the role of Bogor Waqf Forest towards Sustainable Development Goals number 1 (no poverty), and third describe the role of Bogor Waqf Forest number 6 (clean water and sanitation). The data for this study was collected in the field using a qualitative approach with observation, deep interview, and documentation technique. The results of this study show that the establishment of the Bogor Waqf Forest is an idea and a breakthrough in overcoming the rampant problem of forest destruction that occurs. Then, the Bogor Waqf Forest carries out various community empowerment efforts that are aligned with efforts to preserve the forest for the community around the waqf forest. In addition, making water reservoirs and distributing clean water to areas around the forest that are useful needs of people living around the forest. Hence, the impact of Bogor Waqf Forest affected to the local people’s activity and in the distribution of clean water.